The Optimizing Cotton Fiber Quality During the Production Process: Cotton industry - Usmonov, Shukhratjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Cotton fiber quality is a key determinant of textile performance, influencing yarn strength, softness, and fabric durability. This study examines the major factors affecting cotton fiber quality throughout the production chain—from genetic characteristics and environmental influences to agricultural practices and post-harvest handling. Field and laboratory evaluations were conducted to assess how varietal selection, soil fertility, and climate conditions contribute to fiber length, strength, and fineness. The study also analyzed modern technologies such as precision agriculture, biotechnology, and sensor-based monitoring systems that enhance cotton production efficiency and quality.